Effect of Counseling/Modeling on Behaviour Modification of Juvenile Delinquents in Eldoret and Kakamega Rehabilitation Centres - Catherine Nguku W; Kimani Chege; Peter Odera; Ndaita J (European Scientific Journal, ESJ, 2017)
There is a growing concern with the growth and prevalence of Juvenile delinquents (JD) in rehabilitation centres in Kenya. Juvenile delinquency has become an intricate social problem that significantly influences all members and processes of a social structure. In January 2016, Eldoret Juvenile Remand Home alone had 155 juveniles which is its full capacity. It is against this background that this study examined psychotherapeutic interventions in behaviour modification of JD and recommended measures that would increase the effectiveness of psychotherapeutic interventions in rehabilitation centers of JDs in Kenya. The purpose of the study was to determine the effect of counseling on behaviour modification of JD in Eldoret and Kakamega rehabs. The area of study was Eldoret and Kakamega rehabs. The study adopted Merton Functional Theory of Juvenile Delinquency as the theoretical framework. The study adopted the descriptive and explanatory research survey designs. The target population was comprised of delinquents in Kakamega and Eldoret Rehabs, administrators, trainers and counselors in the rehabs and probation officers. A sample size of 149 respondents comprising of 127 JD, 13 trainers, 5 probation officers, 2 counselors and 2 administrators of the Eldoret and Kakamega rehabs participated in the study. Saturated sampling catered for the delinquents, probation officers, rehab administrators and trainers. Research instruments that were used in this study included questionnaires, interview schedule and document analysis. A Pilot study was carried out to ascertain validity and reliability of the instruments and a reliability coefficient of 0.7 was deemed acceptable. Descriptive statistical tools and inferential statistics were used for data analysis. Study findings showed that counseling had a significant effect on behaviour modification. This implies that counseling is an important tool in bringing discipline among juvenile delinquents and for overall rehabilitation programmes which can enhance behaviour modification. There is therefore need for psychotherapeutic intervention at both individual and group level for delinquents so that they can change their behaviour.